Overcoming Clopidogrel Resistance: Three Promising Novel Antiplatelet Drugs Developed in China. Issue 6 (December 2017) - Xie, Hong-Guang; Jia, Yu-Meng; Tai, Ting; Ji, Jin-Zi
Abstract : Abstract: Clopidogrel is one of the most frequently prescribed drugs worldwide; however, the presence of clopidogrel resistance and high susceptibility to genetic variations and drug interactions are facilitating the development of other antiplatelet drugs. To overcome clopidogrel resistance, several promising clopidogrel analogues have been developed in China, such as vicagrel (and its deuterated analogues), PLD-301, and W1. These novel chemical analogues are all characterized by much faster and more efficient bioconversion to clopidogrel thiolactone (or 2-oxo-clopidogrel, the precursor of clopidogrel active metabolite) in the intestine than clopidogrel itself through bypassing the first-step P450-mediated oxidation of clopidogrel in the liver. Of them, metabolic conversion of vicagrel and PLD-301 to 2-oxo-clopidogrel is catalyzed by intestinal carboxylesterase 2 and alkaline phosphatase, respectively. In this review article, we summarized all evidence on highly efficient bioconversion to their shared precursor of clopidogrel active metabolite and the mechanisms underlying such a pronounced improvement. These drugs in the pipeline would be promising antiplatelet drugs that could be superior to clopidogrel in future patient care.